Myricanol modulates skeletal muscle–adipose tissue crosstalk to alleviate high‐fat diet‐induced obesity and insulin resistance. (14th October 2019) - Shen, Shengnan; Liao, Qiwen; Zhang, Tian; Pan, Ruile; Lin, Ligen
Abstract : Background and Purpose: Skeletal muscle is the predominant site for glucose disposal and fatty acid consumption. Emerging evidence indicates that the crosstalk between adipose tissue and skeletal muscle is critical in maintaining insulin sensitivity and lipid homeostasis. The current study was designed to investigate whether myricanol improves insulin sensitivity and alleviates adiposity through modulating skeletal muscle–adipose tissue crosstalk. Experimental Approach: The therapeutic effect of myricanol was evaluated on palmitic acid (PA)‐treated C2C12 myotubes and high‐fat diet (HFD)‐fed mice. The crosstalk between myotubes and adipocytes was evaluated using Transwell assay. The cellular lipid content was examined by Nile red staining. The mitochondrial content was assessed by MitoTracker Green staining and citrate synthase activity, and the mitochondrial function was examined by Seahorse assay. Expression of mitochondria‐related and insulin signalling pathway proteins was analysed by Western blot, and the irisin level was determined by elisa kit. Key Results: Myricanol increased mitochondrial quantity and function through activating AMP‐activated protein kinase, resulting in reduced lipid accumulation and enhanced insulin‐stimulated glucose uptake, in PA‐treated C2C12 myotubes. Furthermore, myricanol stimulated irisin production and secretion from myotubes to reduce lipid content in 3T3‐L1 adipocytes. In HFD‐fed mice, myricanol treatment alleviated adiposity and insulin resistance through enhancing lipid utilization and irisin production in skeletal muscle and inducing browning of inguinal fat. Conclusions and Implications: Myricanol modulates skeletal muscle–adipose tissue crosstalk, to stimulate browning of adipose tissue and improve insulin sensitivity in skeletal muscle. Myricanol might be a potential candidate for treating insulin resistance and obesity.